2021
DOI: 10.26719/emhj.20.136
|View full text |Cite
|
Sign up to set email alerts
|

Translation into Arabic and validation of the Patient Assessment of Care for Chronic Conditions questionnaire for diabetes

Abstract: Background: The Patient Assessment of Care for Chronic Conditions (PACIC-5As) is a questionnaire developed in English and designed to evaluate the health care experiences of people living with chronic conditions such as diabetes. Aims: This study aimed to translate, culturally adapt and validate the PACIC-5As instrument for the Arab context in a sample of Saudi Arabian people with diabetes. Methods: The PACIC-5As was translated into Arabic using a forward and backward translation process. The Arabic version wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 23 publications
1
13
1
Order By: Relevance
“…The mean score on the PACIC instrument suggested that our sample perceived a moderate degree of patient-centredness in their care at the diabetes clinics; these scores were slightly higher than in comparable studies in Saudi Arabia (Alharbi et al, 2021) supports the proposition that providing individualized care may contribute to the self-management of chronic conditions (Rathert et al, 2012). Our findings that PCC did not have a significant relationship with either the physical activity scores (DSMQ) or with HbA1c levels are inconsistent with the results from a study in the USA (Williams et al, 2016).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The mean score on the PACIC instrument suggested that our sample perceived a moderate degree of patient-centredness in their care at the diabetes clinics; these scores were slightly higher than in comparable studies in Saudi Arabia (Alharbi et al, 2021) supports the proposition that providing individualized care may contribute to the self-management of chronic conditions (Rathert et al, 2012). Our findings that PCC did not have a significant relationship with either the physical activity scores (DSMQ) or with HbA1c levels are inconsistent with the results from a study in the USA (Williams et al, 2016).…”
Section: Discussionsupporting
confidence: 72%
“…The mean score on the PACIC instrument suggested that our sample perceived a moderate degree of patient‐centredness in their care at the diabetes clinics; these scores were slightly higher than in comparable studies in Saudi Arabia (Alharbi et al, 2021) and Malaysia (Abdul‐Razak et al, 2018). The relationship between PCC and DSM supports the proposition that providing individualized care may contribute to the self‐management of chronic conditions (Rathert et al, 2012).…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Here, PACIC was selected for this study because it allows for a standardised assessment of the patient’s perspective on the current quality of healthcare services, which is essential in the evaluation of chronic care management [ 22 , 23 ]. The PACIC questionnaire has been validated and used in the Saudi context [ 24 ]. For an estimated patient population of 20,000, the sample size for estimates of PACIC scores with a 5% margin of error at 95% confidence level, was 377 (calculated using a Raosoft calculator) [ 25 ], which was simplified as a target of 400.…”
Section: Methodsmentioning
confidence: 99%
“…[12][13][14] The PACIC questionnaire has been validated and used in the Saudi context. 15,16 The PACIC can be used by health care organisations to support overall quality improvement efforts and track delivery of self-management support for patients. [17][18][19] The key elements of the CCM have been included in NCD management programmes in different healthcare organisations in different countries, such as Australia, Canada, England and the United States.…”
Section: Introductionmentioning
confidence: 99%